Prevalence and related factors of depressive symptoms among HIV/AIDS in Ningbo, China: A cross-sectional study - Chen, Suting; Hong, Hang; Xu, Guozhang (Frontiers in Psychiatry, 2022)
Background: Depressive symptoms were common among HIV/AIDS patients. Previous studies had shown that HIV-infected patients were twice as likely to be diagnosed with depression as the general population. However, only few studies have explored the prevalence and related factors of depression among HIV/AIDS in China. Methods: A cross-sectional study was conducted to study the prevalence of depression among HIV/AIDS from January to December 2021 through the database of HIV/AIDS antiretroviral therapy and psychological evaluation system in Ningbo, China. The Patient Health Questionnaire-2 (PHQ-2) was used to screen for depressive symptoms (PHQ-2 > 0), the Patient Health Questionnaire-9 (PHQ-9) was used to diagnose depression, and multivariate Logistic regression model was carried on to evaluate the related factors. Results: A total of 3939 HIV/AIDS patients were enrolled, and the age of initiation of antiretroviral therapy was (39.54±13.54) years. Among them, 3230 (82.00%) were male, 3844 (97.59%) were Han nationality, 1391 (35.49%) were unmarried, 1665 (42.27%) were homosexual transmission, and 2194 (55.70%) were HIV-infected patients. There were 265 patients (6.73%) with depression, and the proportion of mild, moderate, moderate and severe depression was 4.01% (158/3939), 1.65% (65/3939), 0.76% (30/3939) and 0.30% (12/3939), respectively. Multivariate analysis showed that married [odds ratio (OR): 0.675, 95% CI: 0.501-0.908], divorced or widowed (OR: 0.571, 95% CI: 0.380-1.860), homosexual transmission (OR: 1.793, 95% CI: 1.349-2.396) were associated with depression among HIV/AIDS. Conclusions: The prevalence of depression among HIV/AIDS patients was 6.73% in Ningbo, China. More attention should be paid to the psychological status of unmarried and homosexual HIV/AIDS patients in Ningbo and timely psychological intervention or treatment should be given to those patients with depressive symptoms.